Biocompatibilidade de primers e adesivo utilizados na confecção de próteses maxilofaciais implantorretidas: análise in vitro - Bonatto, Liliane da Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The implant-retained maxillofacial prosthesis can be supported by skin and mucosa. The sub-products produced by the materials used to fabricate these prostheses may act as an irritant factor and cause allergy in these tissues. The aim of this study was to evaluate the cytotoxic effect of primers and adhesive used to bond the acrylic resin and the facial silicone during implant-retained maxillofacial prosthesis fabrication, through the analysis of the cell proliferation, and the production of proinflammatory cytokines and extracellular matrix proteins by keratinocytes. A total of 28 round shape samples (10 x 1 mm) made of resin and silicone bonded or not with primer and adhesive was fabricated. Samples were divided into 7 groups: Resin (R), Silicone (S), Resin + Silastic Medical Adhesive Type A + Silicone (RAS), Resin + DC 1205 primer + Silicone (RDCpS), Resin + Sofreliner primer + Silicone (RSpS), Resin + DC 1205 primer + Silastic Medical Adhesive Type A + Silicone (RDCpAS), and Resin + Sofreliner primer + Silastic Medical Adhesive Type A + Silicone (RSpAS). Extracts of tested materials were prepared setting four samples of each experimental group in Falcon tube with 9mL of medium (Bulbecco's Modified Eagle's) and incubated at 37°C for 24 hours. After incubation period, the extract cytotoxicity was evaluated by an assay of cell survival/proliferation (MTT test) in cultures of human keratinocytes (HaCaT). The levels of IL-1, IL-6 and TNF-α and the chemokine MIP-1α were evaluated by ELISA (Enzyme-Linked Immunoabsorbent Assay). The mRNA expression for MMP-9, TGF-β and collagen type IV were analyzed by the RT-PCR (Real time polymerase chain reaction). Data were submitted to the analysis of variance with Bonferroni post-tests (p<0.05). The results showed increased cell proliferation for the RAS group. The RDCpS group showed the highest...

A prótese bucomaxilofacial implantorretida pode ser suportada por pele ou por mucosa. Subprodutos dos materiais utilizados na confecção destas próteses podem atuar como irritantes ou causadores de reações alérgicas a tais tecidos. A proposta do presente estudo foi avaliar a citotoxicidade de primers e adesivo utilizados na confecção de próteses maxilofaciais retidas por implantes, por meio da análise da proliferação celular e da produção de citocinas pró-inflamatórias e de proteínas de matriz extracelular por queratinócitos humanos. Foram confeccionadas 28 amostras de resina e silicone, em forma de discos (10 x 1 mm), unidas ou não pela aplicação de primer e/ou adesivo. Estas amostras foram distribuídas em 7 grupos: Resina (R), Silicone (S), Resina + Silastic Medhical Adhesive Type A + Silicone (RAS), Resina + DC 1205 primer + Silicone (RDCpS), Resina + Sofreliner primer + Silicone (RSpS), Resina + DC 1205 primer + Silastic Medhical Adhesive Type A + Silicone (RDCpAS) e Resina + Sofreliner primer + Silastic Medhical Adhesive Type A + Silicone (RSpAS). Os extratos dos materiais testados foram preparados colocando-se quatro amostras de cada grupo experimental em tubos de ensaio contendo 9 mL de meio de cultura DMEM (Dulbecco's Modified Eagle's) e incubados a 37°C por 24 horas. Após o período de incubação, a citotoxicidade dos extratos foi avaliada pelo ensaio de MTT em cultura de queratinócitos humanos (HaCaT). Foi avaliada, também, a produção das citocinas IL-1, IL-6 e TNF-α e a quimiocina MIP-1α por meio do ensaio ELISA (Ensaio Imunoabsorbente de Ligação Enzimática). Também foi avaliada a expressão de RNAm para MMP-9, TGF-β e COL-IV por meio da técnica de RT-PCR em tempo real (Reação em Cadeia da Polimerase em Tempo Real). Os dados obtidos foram submetidos à Análise de Variância (ANOVA), seguido...
Keywords: Citotoxicidade imunológica; Prótese maxilofacial; Resinas acrílicas; Elastômeros de silicone; Teste de materiais; Cytotoxicity, Immunologic